Long term performance of certain ortets and hybrid clones of Hevea brasiliensis in a high altitude region in Kerala, India - Lakshmanan, Radha; Meenakumari, T.; Thomas, Vinoth (Journal of Plantation Crops, 2020)
Long term performance of four hybrid Hevea clones and ten ortet selections including nine from a high elevation site within the traditional rubber growing tract of Kerala was studied. Significant variability was observed among the hybrids and ortets for all major agronomic traits. Growth of rubber trees was invariably poor in the high altitude region and tappability by the tenth year of planting was less than 50 per cent. The hybrid clones RRII 203 and RRIC 100 showed highest growth vigour with 80 per cent tappability by the 13th year of planting. Among the ortets, P 270 and Iritty 1 recorded the highest tappability of 64 per cent. The ortet P 270 was the best performer with the highest girth at the opening (61 cm), girth increment during immaturity (5.5 cm) on tapping (3.4 cm) and bole volume (0.1 m3). RRII 203 was the highest yielding clone with 56 g tree-1 tap-1 over eight years of tapping. High annual yield (48 g tree-1 tap-1) and lean season yield of P 270 combined with high drc on par with the highest yielding clone RRII 203 indicated the specific adaptability of this ortet to high elevation areas. The ortets P 213 and Iritty 1 and hybrid clone RRIC 100 were the other promising clones exhibiting growth adaptation and high yield potential under high altitude conditions.